First-in-Human, Double-Blind, Randomized, Placebo-Controlled Trial of TQ-F3083, a New Dipeptidyl Peptidase-4 Inhibitor, in Healthy Chinese Adults - Liu, Jingrui; Zhu, Xiaoxue; Zhang, Hong; Wei, Haijing; Yang, Deming; Xu, Zhongnan; Huo, Dandan; Li, Xiaojiao; Ding, Yanhua (Frontiers in Pharmacology, 2021)
Abstract Background: As a novel dipeptidyl peptidase-4 (DPP-4) inhibitor, TQ-F3083 represents a promising new drug for type 2 diabetes mellitus (T2DM). This phase I, first-in-human study evaluated the tolerability, pharmacokinetics and pharmacodynamics of TQ-F3083 in healthy Chinese adults. Methods: Sixty healthy participants total were enrolled in the single-ascending dose, multiple-dose, and food-effect studies. Safety endpoints included adverse events (AEs), vital signs, 12-lead electrocardiogram, abdominal ultrasound, chest X-ray, physical examination, and clinical laboratory tests. Blood, urine, and feces samples were collected for pharmacokinetic analyses. Pharmacodynamic parameters were evaluated based on DPP-4 activity and the active glucagon-like peptide-1 concentration. Results: In total, 22 treatment-related AEs, mostly grade 1 or 2, were reported in 14 individuals. No deaths, serious AEs, or grade ≥4 AEs occurred, and no dose-dependent AEs were demonstrated. For pharmacokinetic characteristics, dose linearity was analyzed using power model. The slopes (90% CIs) were 1.08 (1.02-1.13) and 1.05 (0.99-1.11) for AUC0-t and AUC0-∞, suggesting liner pharmacokinetic characteristic after oral dose TQ-F3083 from 2-160 mg. The accumulation factor was 1.39 after multiple dose for 7 days. Decreased plasma exposure (84.87% decrease in Cmax, 49.23% in AUC0-t and 47.77% in AUC0-∞) were observed with administration after a high-fat and high-calorie standardized breakfast. The 0–72 h TQ-F3083 excretion recovery percentages were 7.84% in urine and 5.76% in feces. Over 80% DPP-4 inhibition for 24 h was observed in the 20–160 mg cohorts, and the model-estimated 50% effective concentration was 1.10 ng/ml. The concentration of active glucagon-like peptide-1 increased after TQ-F3083 administration, but no obvious dose dependency was observed. Conclusion: TQ-F3083 was well tolerated in healthy Chinese adults, and the pharmacokinetic and pharmacodynamic characteristics support further evaluation of TQ-F3083 in a trial in T2DM patients.